Heterosis for yield and component traits in safflower (Carthamus tinctorius L.): Heterosis for yield and component traits in safflower (Carthamus tinctorius L.) - P B WADIKAR,; S L DHARE,; S L WAGHMODE, (Journal of Oilseeds Research, 2020)
The present study in safflower revealed that for all the characters investigated in 15 crosses, heterosis was noticed in both positive and negative directions indicating that genes with negative as well as positive effects were involved in trait manifestations. Among 15 crosses, the cross GMU-2720 x GMU-3423 for number of branches/plant, number capitulum/plant showed highest significant and positive heterobeltiosis and standard heterosis in desirable direction. PBNS-12 x GMU-3431 for number of seed/capitulum; GMU-2720 x GMU-3423 for seed yield/plant and GMU-1339 x GMU-3423 for oil content showed highest significant and positive standard heterosis in desirable direction. Thus, five crosses GMU-2720 x GMU-3423, GMU-1339 x PBN-96, GMU-1339 x EC-757665, GMU-1339 x EC-757665 and PBNS-12 x EC-757665, showed maximum standard heterosis in desired direction for majority of the characters.